Atomic Mechanism of Arsenic Monolayer Doping on oxide-free Silicon(111). Issue 33 (20th June 2016) - Longo, Roberto C.; Mattson, Eric C.; Vega, Abraham; Cabrera, Wilfredo; Cho, Kyeongjae; Chabal, Yves; Thissen, Peter
Abstract: The reaction pathway for shallow arsenic doping of silicon by methylarsenic acid molecules directly grafted on oxide-free, H-terminated Si(111) surfaces is unraveled combining Infrared absorption spectroscopy, X-ray Photoelectron Spectroscopy, Low Energy Ion Scattering and ab initio Molecular Dynamics simulations. The overall driving force is identified as a thermodynamic instability of As +5 in contact with silicon, which initiates a self-decomposition of chemisorbed methylarsenic molecules at ∼600 K. As the temperature is increased, the As-C bond breaks – the weakest link of the adsorbed molecule – with release of the organic ligand and a rearrangement from a monodentate to a bidentate bonding configuration. In this process, oxygen atoms evolve by partial desorption as H2 O and partial incorporation into the surface Si atom backbonds. At ∼1050 K, diffusion of As into the sub-surface region of silicon is observed. There is no evidence for As desorption and no remaining C contamination.